Cytotoxic and apoptotic potential of Myristica fragrans Houtt. (mace) extract on human oral epidermal carcinoma KB cell lines - Gayathri Rengasamy; Anuradha Venkataraman; Vishnu Priya Veeraraghavan; Mallika Jainu (Universidade de São Paulo, 2018)
Several studies have revealed that certain naturally occurring medicinal plants inhibit the growth of various cancers. The present study was conducted to evaluate cytotoxicity and apoptotic induction potential of Myristica fragrans Houtt mace extract. The cytotoxic activity of the Myristica fragrans Houtt mace acetone extract was assayed by MTT assay on human oral epidermal carcinoma KB cell lines. KB cells were incubated with different concentration of mace extract ranging from 25 to 125 μg/mL for 24hrs. The apoptotic induction potential was also studied by the analysis of Bcl-2 protein and gene expression in mace extract incubated KB cell lines using western blotting technique and real-time polymerase chain reaction. The mace extract exhibited cytotoxicity and anticancer effect against KB cell lines and it also suppressed the growth of cancer cells, therefore growth inhibitory effect was noted in extract treated cell lines. The apoptotic potential of mace extract was accompanied by reduced gene expression of Bcl-2 compared to the untreated KB cells. The mace extract shows the cytotoxic activity and induced the apoptosis through the modulation of its target genes Bcl-2 in the KB cell lines, suggesting the potential of mace as a candidate for oral cancer chemoprevention. This can be further investigated in vivo for its anticancer potential.